Pelatihan Peningkatan Kreativitas dan Semangat Wirausaha Siswa SMK Bina Profesi Pekanbaru - Elida Gultom; Nova Syafrina; Lamin Lamin; Jeli Nata Liyas (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
This community service was carried out on students of the Bina Profesi Pekanbaru Vocational High School, Riau Province. This activity was carried out on Wednesday, January 15, 2025 with the theme of Training to improve creativity and entrepreneurial spirit of Bina Profesi Pekanbaru Vocational High School students. The purpose of this service is to increase creativity and entrepreneurial spirit for Bina Profesi Pekanbaru Vocational High School students as capital for students in facing challenges in the world of work and business. Vocational high school students will be better prepared to compete and create their own business opportunities. With creativity and enthusiasm, vocational high school students will become not only ready-to-use workers but also innovative and independent prospective entrepreneurs. The method of implementing this service is carried out in two ways, namely the lecture method and practice. The results of this community service activity are expected to increase the creativity and entrepreneurial spirit of Bina Profesi Pekanbaru Vocational High School students.